Aqua bill store mineral water sales application program - Ayshwarya B.; Nguyen P.T.; Al Bazar F.; Aminudin N.; Shankar K.; Hashim W.; Gorina L.N.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Technology development is faster. Technology is also increasing to be used by large and small companies. But it's different from the Aqua Bill Store located at Pringsewu Regency. This store has not used the sales application program, so that they experience obstacle in making sales report and need an application to sell mineral water. This research aimed to design an application for the mineral water sales at Aqua Bill Store. System is designed using Visual Basic 6.0 programming language. The result of this study was this application system that helps employees in the process of making sales reports and data storage besides that it also eases for business owners to check items so they can avoid depletion of goods stock. BEIESP.